High school football player experiences with multiple injuries: a qualitative biopsychosocial model application - Golub, Natalie; Steinfeldt, Jesse A. (Frontiers in Sports and Active Living, 2025)
IntroductionHigh school athletes in the United States sustain approximately 1.3 million sport-related injuries annually, with nearly half occurring in football. These injuries can significantly impact athletes' psychological and behavioral well-being, influenced by factors such as athletic identity, self-efficacy, prosocial behavior, and prior injury history. While the Biopsychosocial Model of Sport Injury Rehabilitation offers a comprehensive framework for understanding injury recovery, limited research has examined how athletes respond to multiple injuries over time.MethodsThis qualitative study applied the Biopsychosocial Model to explore the lived experiences of eight male high school football players who sustained multiple injuries during a single season. Each participant missed at least one week of play and/or one game per injury. Semi-structured interviews were conducted to investigate emotional responses, perceived social support, and stress management. Thematic analysis was used to analyze the data, following an inductive approach that allowed themes to emerge organically from participants' narratives.ResultsParticipants shared detailed accounts of their injuries, recovery processes, and the broader impacts on their lives. Thematic analysis revealed four overarching themes: (a) emotional response, (b) sources of support, (c) stress effects, and (d) coping strategies. Athletes described a wide range of emotional and behavioral responses, including frustration, anxiety, and determination. Support systems—such as family, coaches, and teammates—played a critical role in their recovery. Stress related to performance, identity, and future prospects was common, and athletes employed various coping mechanisms, including mental reframing, goal setting, and seeking social support. These responses were shaped by individual injury histories and personal resilience.DiscussionThe findings highlight the complex and varied ways high school football players experience and manage multiple injuries. Emotional reactions, support networks, and coping strategies all play a role in shaping recovery outcomes. Understanding these lived experiences can inform more holistic and personalized approaches to injury rehabilitation. Interventions that address emotional well-being, enhance social support, and promote effective coping strategies may improve recovery and reduce the risk of future injuries.